AN ERROR ANALYSIS OF USING SIMPLE PRESENT TENSE IN DESCRIPTIVE TEXT WRITTEN BY THE SEVENTH GRADES STUDENTS OF SMP HUTAMA BEKASI IN THE ACADEMIC YEAR 2017/2018 - Poppy Guswita (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
The seventh grades students have to learn descriptive text. It means that they also have to learn simple present tense as a tense they used in writing descriptive text. But writing is no easy for them. They have some errors in they written especially in taxonomy structure, such as omission, addition, misformation, misordering. Using descriptive text written by the seventh grades students of SMP Hutama Bekasi, as many as 21 students, this study analyzes the types of errors in the use of simple present tense. In this research, researcher uses qualitative method by using descriptive qualitative approach that Researchers find that misformation (48,96%) is the most error which students made in their written. The misformation of alternating form is the dominant error and it shows that students lack of English grammatical mastery especially in selection pronouns.